1999
DOI: 10.1111/1468-2419.00079
|View full text |Cite
|
Sign up to set email alerts
|

Components of effective diversity training programmes

Abstract: This article reports on the results of a study on the components of effective diversity training programmes as perceived by diversity experts. The major method of this research study was in-depth, open-ended telephone interviews with a panel of 12 diversity experts located throughout the USA. The purpose was to draw upon their knowledgeable insights about the topic of effective diversity training programmes. The literature that this study was based on shows that organisations have to consider training for dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 7 publications
1
33
0
Order By: Relevance
“…Trainers use diversity training as a means to meet many objectives, such as attracting and retaining customers and productive workers; maintaining high employee morale; and/or fostering understanding and harmony between workers (Wentling & Palma-Rivas, 1999). Some programs are designed to ensure a desired workforce composition that includes underrepresented groups.…”
Section: Contemporary Perspectives On Diversity Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Trainers use diversity training as a means to meet many objectives, such as attracting and retaining customers and productive workers; maintaining high employee morale; and/or fostering understanding and harmony between workers (Wentling & Palma-Rivas, 1999). Some programs are designed to ensure a desired workforce composition that includes underrepresented groups.…”
Section: Contemporary Perspectives On Diversity Trainingmentioning
confidence: 99%
“…For example, Nextel Communications calculated (through participant surveys) a 9.7% increase in retention as a result of its diversity awareness training program, and an overall 163% return on investment (ROI) from the program ("Getting Results from Diversity Training," 2003). Regardless of the objectives, periodic training programs are by far the most commonly used diversity activity (Wentling & Palma-Rivas, 1999). Unfortunately, periodic training programs often fail or fall short of meeting the intended outcomes.…”
Section: Contemporary Perspectives On Diversity Trainingmentioning
confidence: 99%
“…Awareness can be achieved through many processes; yet, training is one of the most prevalent methods. In developing their model, Avery and Thomas (2004, p.383) noted that 'successful diversity training appears to involve practice communicating with dissimilar others and increasing participant's awareness of diversity issues and how they contribute to a more positive work environment' as also cited by Chrobot-Mason and Quinones (2002) and Wentling and Palma-Rivas (1999).…”
Section: Diversity Management Competencymentioning
confidence: 99%
“…Being employed by an organisation that is composed of diverse faculty, diversity training could be a critical element in maintaining a positive work environment. According to Wentling and Palma-Rivas (1999), diversity training is defined as 'the process by which a workforce is educated about cultural, socio-economic, racial and religious differences among employees and taught how to embrace those differences so as to create and maintain an effective work environment' (Lai and Kleiner, 2001). Participation in diversity training may encourage faculty within the academic community to take what they learn and apply it on the job.…”
Section: Diversity Trainingmentioning
confidence: 99%
“…These findings are echoed by another research that focuses on what diversity training specialists themselves think about the factors that influence the effectiveness of the training session they organize. Wentling and Palma-Rivas (1999) found that 100% of the interviewed diversity trainers judged that the most important factor for effectiveness of a diversity training session is ''commitment and support from top management'', followed by the fact that diversity training is ''included as part of the organisational strategic plan' ' (1999, p. 221).…”
Section: Confrontation With One's Own Stereotypesmentioning
confidence: 99%